2020
DOI: 10.1016/j.addma.2020.101297
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer bonding has bulk-material strength in extrusion additive manufacturing: New understanding of anisotropy

Abstract: The deposited filament, from which the 3d printed specimens are comprised (sometimes referred to as rasters, fibres, roads, tracks or extrudates in other studies). Extruded-filament geometry:The cross-sectional geometry of the extruded filament.EFW: Extruded-filament width F: Filament direction (sometimes referred to as longitudinal direction in other studies -parallel to the print bed)Interface: The region of joining between two extruded filaments. Interlayer bonding:The interfacial bonding between layers (ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
77
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(92 citation statements)
references
References 41 publications
(114 reference statements)
14
77
0
1
Order By: Relevance
“…With FullControl, the band required no post-processing because it was printed with a single pass of the nozzle, extruding 250% of the nozzle diameter (aspect ratio of 5 for width:layer-height). This was found to achieve a solid structure with good mechanical integrity, as expected based on recent understanding that a wider aspect ratio for filament cross-sections improves mechanical performance [37] (discussed in Section 4.1). Due to improved mechanical integrity, it was possible to reduce weight by 20% whilst maintaining equivalent or improved performance.…”
Section: Industrial Manufacturingsupporting
confidence: 73%
See 1 more Smart Citation
“…With FullControl, the band required no post-processing because it was printed with a single pass of the nozzle, extruding 250% of the nozzle diameter (aspect ratio of 5 for width:layer-height). This was found to achieve a solid structure with good mechanical integrity, as expected based on recent understanding that a wider aspect ratio for filament cross-sections improves mechanical performance [37] (discussed in Section 4.1). Due to improved mechanical integrity, it was possible to reduce weight by 20% whilst maintaining equivalent or improved performance.…”
Section: Industrial Manufacturingsupporting
confidence: 73%
“…That study investigated hundreds of different combinations of speed, acceleration, jerk, retraction, extrusion width, and other parameters. By enabling design geometric tolerances an order of magnitude smaller than the nozzle diameter,, a new micro-tensile-testing specimen was designed with extrusion-widths of filaments carefully controlled to achieve a dog-bone geometry (Figure 4A) [36,37]. This demonstrates the potential to design at completely new scales if process limitations are considered.…”
Section: Process Calibration Characterisation and Hardware Developmentmentioning
confidence: 99%
“…With FullControl, the band required no post-processing because it was printed with a single pass of the nozzle, extruding 250% of the nozzle diameter (aspect ratio of 5 for width:layer-height). This was found to achieve a solid structure with good mechanical integrity, as expected based on recent understanding that a wider aspect ratio for filament cross-sections improves mechanical performance [36] (discussed further in Section 4.1 for micro-tensile-testing specimens). Due to improved mechanical integrity, it was possible to reduce weight by 20% whilst maintaining equivalent or improved performance.…”
supporting
confidence: 70%
“…In other process characterisation research, a new micro-tensile-testing specimen was designed with extrusion-widths of filaments carefully controlled to achieve a dog-bone geometry (Figure 4A) [35,36]. Structures were designed with geometric tolerances an order of magnitude smaller than the nozzle diameter, demonstrating the potential to design at completely new scales if process limitations are considered.…”
Section: Process Calibration Characterisation and Hardware Developmentmentioning
confidence: 99%
“…We performed preliminary mechanical testing on the films produced here and demonstrated that the results are consistent with those obtained from similar films produced using other methods and are also consistent with the anticipated structure and properties of the films. In addition, since the slot die process is an example of a polymer extrusion process, some of which are known to influence the structure and properties of the resulting polymer [ 17 , 18 , 19 ], we performed a very preliminary assessment of the chitosan-only films in terms of direction of extrusion and found no evidence for any such effects.…”
Section: Introductionmentioning
confidence: 99%